PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS III SEKOLAH DASAR - Sarwik Utami (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The purpose of the study is to improve student learning out comes on the subject of "the characteristic and needs of creature" the score obtainned by student is still under the criteria of minimal exhaustiveness that is 70. To achieve the score determined then the authors use the method of media images. This method involves a lot of student activities. Subjects in this study were students of class III A Elementary School 017 Kundur. Data collection procedures by using observation which contains teacher learning procedure consist of learning improvement planning, teacher and student observation data and result of initial and final test. Data analysis uses qualitative data. This study was conducted in two cycles. Every cycle has planning, implementation, observation reflection and assessment. To see pre-cycle student learning outcomes. In pre-cycle, score obtained for the first complete one is 12 people (54,55%) not complete as many as 10 people (45,45%). The first cycle is 15 people (72.73%) and not complete as many as 7 people (27.27%). Cycle II has completed totally 22 people (100%). For the range of score 80 - 89 and the criteria of high assessment. In conclusion, the use of image media methods can improve the results and motivation of students' learning grade III A state elementary school017 Kundur.